Genetic testing in veterinary dermatology. Issue 1 (18th July 2016) - Leeb, Tosso; Müller, Eliane J.; Roosje, Petra; Welle, Monika
Abstract : Background: Molecular genetics has made significant advances in the analysis of hereditary dermatoses during the last several years. Objectives: To provide an update on currently available genetic tests for skin diseases of dogs, cats and horses, and to aid the veterinary clinician in the appropriate selection and applications of genetic tests. Methods: The scientific literature on the topic was critically reviewed. The list of known causative variants for genodermatoses and hair morphology traits was compiled by searching the Online Mendelian Inheritance in Animals (OMIA) database. Results: Genetic testing has become an important diagnostic method in veterinary medicine. Genetic tests can help to establish the correct diagnosis in some diseases with relatively nonspecific signs. Genetic tests are also essential for sustainable breeding programmes and to help minimize the frequency of animals with hereditary diseases. Advances in genetic methodology and bioinformatics already allow genome‐wide screening for potential disease causing mutations for research purposes. It is anticipated that this will become a routine process in clinical practice in the future. Conclusion and clinical importance: As specific DNA tests and broad genome‐wide analyses come into more common use, it is critical that clinicians understand the proper application and interpretation of these test results. Abstract : Background – Molecular genetics has made significant advances in the analysis of hereditary dermatoses during the last several years.Objectives – To provide an update on currently available genetic tests for skin diseases of dogs, cats and horses, and to aid the veterinary clinician in the appropriate selection and applications of genetic tests.Conclusion and clinical importance – As specific DNA tests and broad genome‐wide analyses come into more common use, it is critical that clinicians understand the proper application and interpretation of these test results.